2009
DOI: 10.1002/pc.20785
|View full text |Cite
|
Sign up to set email alerts
|

Influence of yarn texture on the mechanical properties of textile composite castings

Abstract: In this research, mechanical properties of textile composite castings used for immobilizing a damaged limb have been studied. For this purpose, a fabric composite was made using a new knitted fabric and textured yarn for the first time. This composite possesses suitable mechanical properties. Mechanical and physical properties such as tensile, bending, and thickness of materials were studied. Results indicate that the use of textured yarns instead of flat yarns increases the amount of resin retainment in fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the fabric type and fiber orientation have a significant effect on mechanical properties. Zadhoush et al 20 demonstrated that the utilization of textured yarns, as opposed to flat yarns, enhances resin impregnation in fabrics. Additionally, it reduces both the tensile modulus and bending modulus of the fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the fabric type and fiber orientation have a significant effect on mechanical properties. Zadhoush et al 20 demonstrated that the utilization of textured yarns, as opposed to flat yarns, enhances resin impregnation in fabrics. Additionally, it reduces both the tensile modulus and bending modulus of the fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Also, waved fiber can influence the mechanical properties of textile composite castings. 6 As a result of interfacial debonding and discontinuities at fiber ends, short-fiber polymer composites usually have low strength and toughness in comparison with continuous fiber composites. 7 For short fiber composite, load transfer between the fibers and the matrix can be improved by optimization of the fiber shape and a strong interface.…”
Section: Introductionmentioning
confidence: 99%